BENEFÍCIOS DA GINÁSTICA LABORAL PARA INDIVÍDUOS QUE UTILIZAM O COMPUTADOR COMO INSTRUMENTO DE TRABALHO - Coimbra, Pâmela d. S.; Brandli, Keity R.; Marzari, Taline P. (Salão do Conhecimento, 2013)
Resumo